ETIKA BERKOMENTAR MAHASISWA GENERASI Z DI DUNIA MAYA: Perspektif Hadis tentang Amanah dn Husnuzhon - Shinta Adhelia Sugiharto; Sidqi Ali; Nasrulloh Nasrulloh (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2025)
This study examines the ethical behavior of Generation Z students in posting comments in digital spaces through the perspective of hadith, focusing on the values of amanah (trustworthiness) and husnudzon (positive presumption). The purpose of this research is to analyze how these two moral principles are understood and implemented in digital communication, particularly when responding to various types of content on social media. Using a qualitative descriptive method supported by library research, this study explores hadiths related to communication ethics, scholarly literature, and contemporary findings on digital ethics. The results indicate a significant gap between students’ ethical awareness and their actual commenting practices. Although they understand the importance of responsible communication, students often post impulsive comments without adequate verification. The analysis also reveals that integrating the values of amanah and husnudzon can shape more constructive digital interactions by encouraging information verification, reducing negative assumptions, and promoting polite communication. This study emphasizes the importance of strengthening these prophetic values in fostering ethical digital behavior among Generation Z.